Feasibility of a new electronic patient-reported outcome (ePRO) system for an advanced therapy clinical trial in immune-mediated inflammatory disease (PROmics): protocol for a qualitative feasibility study. Issue 9 (6th September 2022) - Hughes, Sarah E; McMullan, Christel; Rowe, Anna; Retzer, Ameeta; Malpass, Rebecca; Bathurst, Camilla; Davies, Elin Haf; Frost, Chris; McNamara, Gary; Harding, Rosie; Price, Gary; Wilson, Roger; et al.
Abstract : Introduction: The use of electronic patient-reported outcome (ePRO) systems to capture PRO data in clinical trials is increasing; however, their feasibility, acceptability and utility in clinical trials of advanced therapy medicinal products (ATMPs) are not yet well understood. This protocol describes a qualitative study that aims to evaluate the feasibility and acceptability of ePRO data capture using a trial-specific ePRO system (the PROmics system) within an advanced therapy trial involving patients with immune-mediated inflammatory disease (rheumatoid arthritis, lupus, primary sclerosing cholangitis (PSC) and Crohn's disease). Methods and analysis: This protocol for a remote, qualitative, interview-based feasibility study is embedded within the POLARISE trial, a single-arm, phase II, multisite ATMP basket trial in the UK. 10–15 patients enrolled in the POLARISE trial and 10–15 research team members at the trial sites will be recruited. Participants will take part in semistructured interviews which will be transcribed verbatim and analysed thematically according to the framework method. Data collection and analysis will occur concurrently and iteratively. Researcher triangulation will be used to achieve a consensus-based analysis, enhancing rigour and trustworthiness. Ethics and dissemination: This study was approved by the London—West London and GTAC Research Ethics Committee (Ref: 21/LO/0475). Informed consent will be obtained from all participants prior to data collection. The study findings will be published in peer-review journals and disseminated via conference presentations and other media. Our patient and public involvement and engagement group and ATMP stakeholder networks will be consulted to maximise dissemination and impact. Trial registration number: ISRCTN80103507 .